Phases. - Musée d'Ixelles, Ixelles (Ixelles : Musée d'Ixelles, 1974)
Avila, Sara ; Appelbaum, Wilfrid ; Besson, Suzanne ; Broisson, Jean ; Beaudonnet, Jean-Louis ; Cavaliere, Alik ; Carlier, Marie ; Chavez, Gerardo ; etc.
Phases, Musée d'Ixelles, 9.10 - 17.11.1974
boek